Ulama and Fatwa (Pros and cons of the Circular Letter of the Aceh Governor and MPU Decree) - Abd. Razak; Nuraini A Manan; Abdul Manan; Rahmat Syahputra (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
This study critically discusses the pros and cons of the circular letter (surat edaran) of the Aceh governor and Ulama Consultative Council (MPU) Decree No. 2 of 2020 related to responses and public evaluation of the prohibition of the religious learning forums (pengajian) other than Ahlussunnah Waljama’ah. This research is a qualitative research with three data collection techniques: meticulous observation, in-depth interviews, and documentation. The result of the study showed that there were pros and cons related to the circular letter and decision on the prohibition of conducting pengajian that contradicts the I’tiqat of Ahlussunnah Waljama’ah which is based on Syafi’i School of Law. Among them, according to the Aceh government and the MPU, the circular letter is intended to prevent greater abuses in the form of disunity in the Acehnese community due to differences in understanding in matters of worship. Meanwhile, others failed to understand the circular letter and MPU decrees because they consider them weak and were greatly influenced by certain conservative Islamic figures in Aceh, appearing to some people as political activity and power.